Seromas Following Pediatric Spinal Deformity Surgery: Is Operative Management Necessary?. Issue 4 (April 2020) - Yu, James; Dumaine, Anne M.; Poe-Kochert, Connie; Thompson, George H.; Mistovich, R. Justin
Abstract : Background: Seromas are known complications after pediatric spinal deformity surgery. Although many surgeons perform an early debridement to prevent deep surgical site infections (SSIs), a less invasive approach to seroma management has not been studied. We hypothesized that a conservative approach to seroma management would be safe and yield equivalent outcomes. Methods: We performed a retrospective review of patients who developed a postoperative seroma with or without nonpurulent drainage. Inclusion criteria were patients below 21 years who underwent primary posterior spinal fusion from 1996 to 2016 and developed a postoperative wound seroma. Seromas were clinically defined as an afebrile patient with a fluid collection that was soft and nontender to palpation and without induration or erythema. Growing spine surgeries and revision procedures were excluded from this study. Results: Twenty-five of 790 total patients with a mean follow-up of 57.8 months (±48.5 mo) developed a seroma. Seromas were identified at a mean of 13.6 days postoperatively and resolved after a mean of 12.2 days following the presentation. Seromas occurred in 12 patients with idiopathic scoliosis, 12 with neuromuscular scoliosis, and 1 patient with Scheuermann kyphosis. All cases were managed conservatively with monitoring of the incision without an operative procedure. In cases of spontaneous drainage, a sterile dressing was applied to the wound and changed as needed until drainage ceased. Two patients underwent bedside needle aspiration and 5 patients received prophylactic antibiotics at the treating surgeon's discretion. All cases resolved spontaneously without development of an acute SSI. Three cases subsequently developed a late SSI (range, 18 to 38 mo postoperatively). Two had idiopathic scoliosis and 1 had neuromuscular scoliosis. None of these seromas drained spontaneously. Conclusions: Conservative management of postoperative seromas after pediatric spinal deformity surgery is appropriate. It is unclear if seromas contributed to the development of the 3 late infections. Further studies are needed regarding the relationship of late infections in seroma patients. Level of Evidence: Level IV—case series.